Penciptaan Iklim Dan Etos Kerja Yang Kondusif Dalam Proses Pembelajaran - Erlina Siregar (Proceedings of Annual Conference on Islamic Educational Management, 2021)
The success of teaching a teacher can be determined by several factors, one of the factors that influence the success of teaching a teacher is the work climate or the place where the teacher does the learning process. The working climate as an atmosphere where the teacher does the learning process, needs to be created in such a way that the teacher can feel comfortable, this needs to be done so that the working atmosphere can increase work morale which will ultimately improve teacher performance. At the same time, in addition to the work climate, work ethic is another factor that can improve teacher performance in teaching..